Complexity analysis of Quranic chapters for word cloud generation - Taib, Ibrahim Adham; Che Azemin, Mohd Zulfaezal (Malaysia Technical Scientist Malaysia, 2019)
Word cloud analysis is often used to identify important words within a text. The analysis itself is usually based on frequency analysis, where the most frequent words in a text may be deemed most important. However, words that are frequent may be centered in certain sections only; therefore, it is argued that word cloud analysis based on fractal dimension would be more effective at identifying important words. This study compared word cloud analyses on Chapter Yusuf and Chapter Yunus of the Quran using frequency and fractal dimension. This study found that both approaches were quite similar, but differ in some ways as well. The findings would require validation according to exegesis of the Quran.